Genome analysis and prevalence of SARS-CoV-2 Indonesian variants and the correlation with the outbreak timeline - Maria Prevyolita Indra Muliawan; Timotius Christopher Tantokusumo; Amalda Siti Anisa; Kholis Abdurachim Audah (Indonesian Society for Biochemistry and Molecular Biology, 2024)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has undergone multiple mutations, leading to the development of various variants. Objective: To identify the genetic mutations associated with the transmission and virulence of SARS-CoV-2 variants in Indonesia and to examine their correlation with the outbreak timeline. Methods: We analyzed whole genome sequences of SARS-CoV-2 wild type and variants isolated from Indonesian samples, sourced from GenBank and the GISAID EpiCoV database. The spike glycoprotein gene sequences were examined using the BLAST to identify nucleotide and amino acid changes. Additionally, we investigated the prevalence of these variants and their submission timelines on the GISAID database, correlating them with the outbreak timeline. Results: Our analysis identified nine amino acid changes in the alpha, beta, and delta variants, and three in the gamma variant, compared to the wild type. A correlation between the submission timelines of SARS-CoV-2 variants and the outbreak timeline indicated that the delta variant (B.1.617.2) likely contributed to the surge in COVID-19 cases from July to September 2021. Conclusion: Mutations were detected in each variant, emerging at distinct times, and are likely to influence transmission rates and virulence.